TINJAUAN HUKUM ISLAM TERHADAP SAMBUNG BULU MATA, SULAM ALIS DAN SULAM BIBIR (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
Look beautiful is the desire of almost every woman from the heart and appearance. Today’s there are more of beauty trends from only make up tools to performing operations at certain points, such a facial plastic surgery, nose surgery and others. Recently a new term has emerged with the trend of beauty eyelashes extensions, eyebrow embroidery and lip embroidery. Eyelashes extension is the process of (extension) artificial eyelashes to the original eyelashes one by one with special glue, so that the eyelashes looks longer and thicker and more pliable. Eyebrow embroidery is a cosmetic procedure for filling eyebrows by implanting colored pigments with a texture resembling real haur following the original hair growth path so that the eyebrows looks more beautiful. Lip embridery is a method for bautifiying the colour and shape of lips. Lip embroidery is made of semi-permanent ink that is by injecting the ink according to what a customer want, besides as a way of reducing the lips, the lip embroidery can also change the shape of lips to be thinner or thicker. Keywords: Islamic Law, Beauty Trends, Eyelashes extensions, Eyebrow Embroidery, Lip Embroidery